2002
DOI: 10.1126/science.1073885
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Potential Ejaculation Generator in the Spinal Cord

Abstract: We tested the significance of a population of lumbar spinothalamic cells for male sexual behavior in rats. These cells are positioned to relay ejaculation-related signals from reproductive organs to the brain, and they express neurokinin-1 receptors. Ablation of these neurons by the selective toxin SSP-saporin resulted in a complete disruption of ejaculatory behavior. In contrast, other components of sexual behavior remained intact. These results suggest that this population of spinothalamic cells plays a pivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
248
2
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(266 citation statements)
references
References 10 publications
11
248
2
5
Order By: Relevance
“…An ejaculation generator in the lumbar spinal cord comprises galanin-and cholecystokinin (CCK)-containing neurons, which showed Fos-ir only after ejaculating (Truitt and Coolen, 2002;Truitt et al, 2003). Lesions of these neurons severely impaired ejaculation; therefore, they not only carry ejaculation-specific sensory input to the brain, but also elicit ejaculation (Truitt and Coolen, 2002).…”
Section: Ne Antagonists − (Clark and Smith 1990)mentioning
confidence: 99%
See 1 more Smart Citation
“…An ejaculation generator in the lumbar spinal cord comprises galanin-and cholecystokinin (CCK)-containing neurons, which showed Fos-ir only after ejaculating (Truitt and Coolen, 2002;Truitt et al, 2003). Lesions of these neurons severely impaired ejaculation; therefore, they not only carry ejaculation-specific sensory input to the brain, but also elicit ejaculation (Truitt and Coolen, 2002).…”
Section: Ne Antagonists − (Clark and Smith 1990)mentioning
confidence: 99%
“…Lesions of these neurons severely impaired ejaculation; therefore, they not only carry ejaculation-specific sensory input to the brain, but also elicit ejaculation (Truitt and Coolen, 2002).…”
Section: Ne Antagonists − (Clark and Smith 1990)mentioning
confidence: 99%
“…This development seems to coincide with a specific interest to perform clinical and basic research on the mechanisms driving premature ejaculation, for example, a tendency to focus on the sensory input of tactile stimuli (eg sensitivity of the glans penis and evoked potentials of peripheral neurons) in the far East, 91,92 in contrast, a tendency to focus on the motoric output (eg serotonergic brain and spinal cord areas) in Western countries. 4,5,93 It is of relevance to note that, in studies on ointments in the Far East, a 3 min criterion seems in use, in contrast to the 1-2 min inclusion criterion in drug treatments in Western countries.…”
Section: Pharmacological Considerationsmentioning
confidence: 99%
“…Tactile sensations from the penis are relayed to MPOA via the midbrain subparafascicular nucleus (SPF), which also sends projections to Me (Greco et al, 1998;Truitt and Coolen, 2002;Coolen et al, 2003;Truitt et al, 2003). Although chemosensory cues activate Fos in MPOA and Me, a subset of neurons within an interconnected circuit of the MPN, posterior Me, and SPF is activated only following ejaculation (Coolen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Chemosensory cues from the olfactory mucosa and vomeronasal organs are essential for male hamster sexual behavior (Murphy and Schneider, 1970), and previous studies have established that chemosensory stimuli elicit DA release in various brain regions in male rodents (Pfaus et al, 1990;Damsma et al, 1992;Hull et al, 1995;Schulz et al, 2003). However, MPOA also receives other sensory stimuli during mating, including ascending somatosensory input from the penis (Greco et al, 1998;Truitt and Coolen, 2002;Coolen et al, 2003;Truitt et al, 2003). While previous studies have shown that chemosensory cues alone are sufficient for DA release in MPOA, whether chemosensory stimuli are essential for MPOA DA release during mating has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%